Rabson-Mendenhall syndrome in a 6-year-old girl. - Novoa, M.P.; Hernandez, J.F.; Florez, J. (European Journal of Pediatric Dermatology, 2022)
Many factors such as obesity, growth hormone, glucagon and genetic defects are possible causes of insulin resistance, which results in a non-optimal response of the glucose metabolism and therefore an increased release of insulin. Insulin resistance is of a higher degree when it is linked to a genetic syndrome. Genetic syndromes of varying severity associated with insulin resistance have been identified (2, 3), ranging from the severe phenotype of Donohue syndrome to the milder phenotype of Rabson-Mendenhall syndrome. Patients initially have normal blood glucose values with concomitant increase in insulin levels; these changes are due to INRS mutations with impaired insulin clearance; a small percentage of patients have autoantibodies against INRS, which are responsible for impaired glycemic control […].